Manipulation of chirurgical robot by means of a natural interface - Vargas-Rosero, H. F.; Vivas-Albán, O. A. (Revista Mexicana de Ingenieria Biomedica, 2016)
This paper presents the implementation of a virtual surgical simulator governed by the natural interface through Leap Motion to determine the feasibility of using this interface in this area. The simulator comprises three robots one of which handles the endoscope into the patient’s abdomen, and the others are surgical robots. A method of laparoscopic cholecystectomy (removal of the gallbladder) was developed, which targets through a joystick or natural interface. The application allows some actions such as opening or closing crow bill, locate clips, make cuts and guide the instruments. Additionally, this tool was tested by surgery students, obtaining a better degree of satisfaction with the use of a natural interface.